Bibliometric Analysis Reveals a 20-Year Research Trend for Chemotherapy-Induced Peripheral Neuropathy - Gu, Jialin; Hu, Miao; Gu, Zhancheng; Yu, Jialin; Ji, Yi; Li, Lingchang; Hu, Canhong; Wei, Guoli; Huo, Jiege (Frontiers in Neurology, 2022)
Objective: Much research has focused on the field of chemotherapy-induced peripheral neuropathy (CIPN). In this study, we performed a bibliometric analysis of CIPN-related publications to identify key research areas and trends over the last 20 years. Methods: We searched the Web of Science core collection for publications relating to CIPN that were published between January 2001 and September 2021. We then performed bibliometric analysis and visualization using Microsoft Excel 2019, VOSviewer, and the Bibliometric online analysis platform (https://bibliometric.com/). Results: In total, we identified 2,188 eligible publications in the field of CIPN, with an increasing trend in the annual number of publications. The USA and Italy were dominant in the CIPN field. Supportive Care in Cancer was the most productive journal. G. Cavaletti and A.A. Argyriou published the largest number of papers. Of all institutions, the University of Milano-Bicocca, Italy, published the highest number of papers. Analysis of the co-occurrence of keywords revealed the specific characteristics relating to the four main clusters: oxaliplatin, paclitaxel, pain management, and quality of life. Newly emerging research focusses predominantly on neuroinflammatory mechanisms and non-pharmacological interventions for CIPN. Conclusion: This bibliometric study reviewed the evolutionary trends in CIPN research and identified current research hotspots and research trends. We also identified journals, institutions, and authors, with the highest levels of impact to enhance collaboration and learning.